Changing socio-cognitive frames through anti-genderviolence metaphors in Spain: a multimodal metaphor analysis - Muelas Gil, María; Romano Mozo, Manuela (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2023)
Violence against women is one of 4th Wave Feminism’s main worries. Feminist journalists and discourse analysts insist that, when addressing gender violence, a new discourse of solidarity and hope, rather than the traditional one of danger and threat, needs to be deployed; and this new discourse seems to be already permeating institutional anti-gender violence campaigns. Drawing on critical and socio-cognitive approaches to discourse, this paper focuses on how the struggle against gender violence is conceptualized by Spanish Institutions as represented in posters for November 25 (International Day for the Elimination of Violence Against Women) from 2005 to 2022. More specifically, we use the concepts of (multimodal) metaphorical creativity, metaphor scenario and metaphorical polarization to analyze how different scenarios or narratives are created in the posters under study. Preliminary results show how: (i) the use of metaphorical strategies increases throughout the 20 years studied; (ii) there is a shift in the target recipients of the texts, gradually moving from women to society in general, including men; (iii) the metaphor scenarios identified focus mainly on action, exhorting women to escape and fight gender violence, but also society to get involved, while the danger scenario is decreasing. Results thus show that the new social and cognitive frames related to gender violence developing within the Spanish society, in which women are conceptualized as active citizens and not submissive victims, are being reflected by institutions as well. ----------------------------------------------------------------------------------------------------------- MUDANÇA DE QUADROS SOCIOCOGNITIVOS ATRAVÉS DE METÁFORAS DE VIOLÊNCIA ANTIGÊNERO NA ESPANHA: UMA ANÁLISE MULTIMODAL DE METÁFORAS A violência contra as mulheres é uma das principais preocupações da 4ª Onda do Feminismo. As jornalistas feministas e os analistas de discurso insistem que, ao abordar a violência de gênero, um novo discurso de solidariedade e esperança, em vez do tradicional de perigo e ameaça, precisa ser implantado; e este novo discurso parece já estar a permear campanhas institucionais de violência antigênero. Baseado em abordagens críticas e sociocognitivas do discurso, este documento centra-se na forma como a luta contra a violência de gênero é conceptualizada por instituições espanholas, tal como representada em cartazes para 25 de Novembro (Dia Internacional para a Eliminação da Violência contra as Mulheres) de 2005 a 2022. Mais especificamente, utilizamos os conceitos de criatividade (multimodal) metafórica, cenário metafórico e polarização metafórica, para analisar como diferentes cenários ou narrativas são criados nos cartazes em estudo. Os resultados preliminares mostram como: (i) o uso de estratégias metafóricas aumenta ao longo dos 20 anos estudados; (ii) há uma mudança nos destinatários-alvo dos textos, passando gradualmente das mulheres para a sociedade em geral, incluindo os homens; (iii) os cenários metafóricos identificados centram-se principalmente na ação, exortando as mulheres a escapar e a combater a violência de gênero, mas também a sociedade a se envolver, enquanto o cenário de perigo está a diminuir. Os resultados mostram assim que os novos frames sociais e cognitivos relacionados com a violência de gênero que se desenvolvem na sociedade espanhola, nos quais as mulheres são conceptualizadas como cidadãs ativas, e não vítimas submissas, estão também sendo refletidos pelas instituições. --- Original em inglês.